2008
DOI: 10.1002/cpp.600
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment as mediator between recollections of childhood and satisfaction with life

Abstract: In accordance with attachment theory, the present study investigates whether internal working models of attachment mediated the association between childhood memories and satisfaction about life in adulthood. A convenient sample of 437 participants completed questionnaires assessing a broad range of childhood memories, working models of attachment and life satisfaction. After controlling for demographics, relational status and living condition, Baron and Kenny's mediation criteria were met for the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 45 publications
1
46
0
3
Order By: Relevance
“…In comparison, adults who have positive childhood experiences often have very high levels of life satisfaction, indicating that individuals who experience childhood sexual trauma may experience lower levels of subjective well-being (Hinnen, Sanderman & Sprangers, 2009). In their study, Hinnen et al, (2009) surveyed 437 participants, primarily female, to assess family context, parental behavior, childhood adversities (i.e. divorce, neglect, abuse), adulthood attachment style and life satisfaction.…”
Section: Attachment Self-esteem and Subjective Well-beingmentioning
confidence: 99%
See 4 more Smart Citations
“…In comparison, adults who have positive childhood experiences often have very high levels of life satisfaction, indicating that individuals who experience childhood sexual trauma may experience lower levels of subjective well-being (Hinnen, Sanderman & Sprangers, 2009). In their study, Hinnen et al, (2009) surveyed 437 participants, primarily female, to assess family context, parental behavior, childhood adversities (i.e. divorce, neglect, abuse), adulthood attachment style and life satisfaction.…”
Section: Attachment Self-esteem and Subjective Well-beingmentioning
confidence: 99%
“…divorce, neglect, abuse), adulthood attachment style and life satisfaction. Results from a regression analysis indicated that childhood memories contributes to adult attachment which in turn ATTACHMENT, SELF-ESTEEM AND SUBJECTIVE WELL-BEING 8 contributes overall subjective well-being (Hinnen et al, 2009). For example, individuals who have history of abuse in childhood are shown to have lower levels of attachment security.…”
Section: Attachment Self-esteem and Subjective Well-beingmentioning
confidence: 99%
See 3 more Smart Citations